2008
DOI: 10.1107/s0108270108023421
|View full text |Cite
|
Sign up to set email alerts
|

Two azo pigments based on β-naphthol

Abstract: There has been much discussion in the literature of the azo-hydrazone tautomerism of pigments. All commercial azo pigments with beta-naphthol as the coupling compound adopt the hydrazone tautomeric form (Ph-NH-N=C) in the solid state. In contrast, the red pigments 1-[4-(dimethylamino)phenyldiazenyl]-2-naphthol, C(18)H(17)N(3)O, (1a), and 1-[4-(diethylamino)phenyldiazenyl]-2-naphthol, C(20)H(21)N(3)O, (1b), have been reported to be azo tautomers or a mixture of azo and hydrazone tautomers in the solid state. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
4
9
0
Order By: Relevance
“…The pigment exhibits the hydrazone tautomeric form, like all industrial hydrazone pigments (formerly known as 'azo pigments') (Gilli et al, 2005;Schmidt et al, 2008;Hunger & Schmidt, 2018). The N-H group forms two intramolecular [S 1 1 (6)] N-HÁ Á ÁO hydrogen bonds (Table 1).…”
Section: Structural Commentarymentioning
confidence: 97%
“…The pigment exhibits the hydrazone tautomeric form, like all industrial hydrazone pigments (formerly known as 'azo pigments') (Gilli et al, 2005;Schmidt et al, 2008;Hunger & Schmidt, 2018). The N-H group forms two intramolecular [S 1 1 (6)] N-HÁ Á ÁO hydrogen bonds (Table 1).…”
Section: Structural Commentarymentioning
confidence: 97%
“…This tautomer, AE4, is the next most stable tautomer; therefore, it is concluded that existing of any other tautomer or conformer beside HA1 in a significant amount in the sample is unlikely. The preference for the hydrazone tautomeric forms has been explained by the fact that generally a C@N double bond is energetically more stable than a N@N double bond [19]. However, theoretical calculations [4] suggest that azo-enol tautomers contribute in formation of metal complexes.…”
Section: Conformational Analysis and Tautomerizationmentioning
confidence: 98%
“…This tautomerization is quite interesting from a theoretical standpoint because the two tautomers have different technical properties. In azonaphthols, the equilibrium depends on temperature, the solvent, and the substitution pattern [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%